The Effect of Honey Administration on Gastrohistopathological Image Study In Male White Wistar Rat Induced With Indomethacin - Suprijono, Agus; Trisnadi, Setyo; Negara, Henri Perwira (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2011)
Background: Gastric disorder often generates clinical symptoms such as gastritis or peptic ulcer. Bee honey has high nutrient has been shown to have a protective effect against drugs destroying stomach. The purpose of this study was the difference effect of honey in various concentrations on the gastrohistopathological image in male white Wistar rat induced with indomethacin. Design and Methods: This was an experimental research using control group post test design. 24 male white rats Wistar were randomly divided into 6 groups of 4 mice each. Group I served as the control group (standar and aquades), group II: 3.78 mg of indometachin, group III: 3.78 indomethacin and 3.6 ml honey (25%,) group IV: 3.78 indomethacin 3.6 ml honey (50%,) group V: 3.78 mg indomethacin 3.78 mg and 3.6 ml (75%(), group VI: 3.78 indomethacin 3,78 mg and honey 3.6 ml 100%. Treatment given by sonde once a day for 15 days. the gastrohistopathological image was evaluated for degree of gastritis and degree of peptic ulcer. The data were tested with test Kruskal-Wallis followed by Mann-Whitney test. Results: Kruskal-Wallis test showed at least significant differences in the degree of gastritis and peptic ulcer between between the two groups (p <0.05). Mann-Whitney test howed that not all groups compared to control showed a significant different in the degrees of gastritis and peptic ulcer. Conclusion: The study suggested that honey have effect on the gastrohistopathological image of indomethacin-induced stomach (Sains Medika, 3(1):41-47).